2007
DOI: 10.1080/00071660701302270
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localisation of calbindin D28k in all intestinal segments of the laying hen

Abstract: 1. The aim of the present study was to investigate expression and localisation of a 28-kDa calcium-binding protein (CaBP-D28k) related to active calcium (Ca) absorption, in the entire intestine of egg-laying hens. 2. Western blotting analysis showed that the entire intestine expressed CaBP-D28k to the following degree: duodenum > jejunum > caecum > ileum > colon. Immunohistochemistry showed strong CaBP-D28k localisation in enterocytes along the villus tip-crypt axis in the duodenum and in villus tips in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
5
13
0
Order By: Relevance
“…This result is in line with previous reports that immunoreactive CaBP-D28k was localised in the enterocyte cytoplasm of all intestinal segments in laying hen (Sugiyama et al, 2007). Thus, it is concluded that TRPV6 is expressed strongly in all segments of the intestine of laying hens, and active Ca 2+ transcellular transport may exert significant effects in Ca 2+ absorption from the intestinal lumen during the peak egg-laying stage.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in line with previous reports that immunoreactive CaBP-D28k was localised in the enterocyte cytoplasm of all intestinal segments in laying hen (Sugiyama et al, 2007). Thus, it is concluded that TRPV6 is expressed strongly in all segments of the intestine of laying hens, and active Ca 2+ transcellular transport may exert significant effects in Ca 2+ absorption from the intestinal lumen during the peak egg-laying stage.…”
Section: Discussionsupporting
confidence: 82%
“…Anti-calbindin-k28D positivity in duodenal intestine epithelium corroborates calcium absorption in this region. The greater intensity of positivity in the apical portion of enterocytes corroborates previous studies [41] that cite calbindin-k28D as a cellular calcium transport. This transporter binds to calcium absorbed by the cell and diffuses it into the cytoplasm, which is finally extruded by CA2 + -ATPase into the basolateral membrane, reaching the vascular system through lamina propria vessels [41].…”
Section: Resultssupporting
confidence: 90%
“…In contrast, goblet cells were not positive for anti-calbindin-k28D. These results corroborate the study carried out in layers, which states that in the intestine of layers, there is calbindin-D28k positivity (protein) in all segments, higher in the duodenum and jejunum, especially in the apical portions of the villi, but smaller in the ileum [41, 47].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Layers actively absorb dietary Ca for eggshell formation along the entire gastrointestinal tract (Sugiyama et al, 2007). Whereas absolute Ca retention increases with increasing dietary Ca levels, the efficiency of the absorption process is inversely related to dietary Ca levels (Chandramoni & Sinha, 1998).…”
Section: Introductionmentioning
confidence: 99%